Evaluation of Parking Demand and Future Requirement in the Urban Area - Abbood, Abdulkareem N.; Ahmed, Abdul R. I.; Ajam, Harith K. K. (Civil Engineering Journal, 2021)
Whatever vehicle is traveling, it needs to stop in order to arrive road users their different goals. In most universities, parking becomes an important campus resource, for being as a place to come frequently and to spend long period. Now days parking problems increase with repaid growth of car ownership. So traffic and parking impact can be consider as a major source of contention within any community and can raise additional costs for universities, as well as urban areas facilities. The study aims to evaluate the current parking situation on the university campus in terms of the available supply and required demand of parking spaces in order to recommend future parking spaces need for the next five years. Data has had been collected according to field traffic and engineering survey, Videography method was used for this purpose. Inventories, Interviews and questionnaires included. Data analysis conducted with the aided of AASHTO and equation methods. The study concluded future parking required is 140 vehicle- spaces for the year 2026, according to population rate of growth also illegal parking leads to interference with the movements of pedestrians and their crossing, as well as reducing the capacity of the roads in the study area.Â Doi: 10.28991/cej-2021-03091767 Full Text: PDF